A Negative Correlation Between Expression Profiles of Runt-Related Transcription Factor-2 and Cystine/Glutamate Antiporter xCT Subunit in Ovariectomized Mouse Bone - Kyosuke Uno; Takeshi Takarada; Yukari Nakamura; Hiroyuki Fujita; Eiichi Hinoi; Yukio Yoneda (Elsevier, 2011)
We have previously demonstrated that glutamate (Glu) suppresses cellular proliferation toward self-renewal through a mechanism associated with the depletion of intracellular GSH after promoting the retrograde operation of the bidirectional cystine/Glu antiporter in undifferentiated osteoblastic MC3T3-E1 cells. In this study, we investigated the expression profile of the xCT subunit of the antiporter as well as the master regulator of osteoblastogenesis runt-related transcription factor-2 (Runx2) in ovariectomized mouse bone. In spinal columns isolated 28 days after ovariectomy, a marked reduction was seen with the intensity of Von Kossa staining used as an index of ossification. In femurs of these ovariectomized mice, a significant decrease was seen in mRNA and protein levels of Runx2 along with increased expression of both mRNA and the corresponding protein for the xCT subunit. To evaluate the possible role of the antiporter in osteoblastogenesis, stable transfectants were established with the xCT subunit toward the culture with osteoblastic differentiation inducers in MC3T3-E1 cells. In stable xCT transfectants cultured under differentiation conditions, marked decreases were seen in nodule formation, Ca2+ accumulation, and osteoblastic marker gene expression, in addition to downregulation of both mRNA and the corresponding protein for Runx2. Runx2 promoter activity was markedly stimulated in MC3T3-E1 cells transfected with a responsive promoter plasmid after the culture under differentiation conditions, while transient and stable transfection with xCT expression vector invariably prevented the stimulation through an activator protein-1 site. These results suggest that Runx2 expression would be negatively regulated by the cystine/glutamate antiporter expressed by osteoblastic cells at the level of gene transactivation. Keywords:: osteoblastogenesis, ovariectomy, cystine/glutamate antiporter, xCT subunit, runt-related transcription factor-2 (Runx2)